Metodologias de caracterização de falhas no compressor centrífugo de turbocompressores automotivos - Oscar Ricardo Sandoval Rodríguez (2019)
Internal combustion engines are one of the most widespread technologies in the automotive sector as it impacts factors such as mobility and urban planning. Turbocharging is an effective method in terms of attending international regulations towards emissions and speciﬁc fuel consumption, thus it is expected that this technique will spread around the world, specially in emergent countries. In this scenario, turbocharging demands computational methods that improve systems reliability. In this work three methodologies are developed and applied with the goalofidentifytwotypesoffailureinthecentrifugalcompressorofanautomotiveturbocharger. One failure is related to the compressor’s wheel thinning related to the impact of some foreign object entering, whereas the other to lubrication delay or fault and the erosion caused by water molecules present in the re-circulation of low pressure exhaust gases. Four centrifugal compressors Garrett TA31 were used to compare changes that happen after the failure, these comparisons made with the aid of thermodynamic, rotordynamic and acoustic methodologies. In the thermodynamic methodology two techniques were used to identify the compressor’s wheel degradation. The ﬁrst technique is called geometric characterization, as it aimed in identifying changes in the thermodynamic maps by using geometric parameters. The second technique is called "health state"indices. In the rotordynamic methodology, the vibration of the compressor housingthroughouttheoperationwascharacterizedbyanalyzingitsamplitudesandfrequencies from its discrete Fourier transformation. In the acoustic methodology, an experimental measurementmethodoftheexternalradiationofthecentrifugalcompressortogetherwithanacoustic wave decomposition technique that quantiﬁes its radiated noise was made. The outcome of the geometrictechniqueshowedthatsmallchangesintheoperationalpointswereidentiﬁedbygeometricindices,mainlytheoneswhichpresentedtendenciesofvariationwithagreaterthinning. On the other hand, "health state"indices showed that it was possible to determine degradation in the wheel compressor’s geometry even when static quantities were measured. Regarding the rotordynamic methodology, the three axis of the compressor’s housing presented changes in amplitudes and frequencies when failure wheel occurs, specially in the sub-synchronous frequencyrange. Ontheotherhand,theacousticmethodologypresentedsmallvariations. Finally, this work shows that it was possible to develop computational methods that allow the continual assessment of the centrifugal compressor performance, either by measuring temperature and pressure in the operational point or by the acceleration signal of the set, as in each of these methodologies great changes were observed when compared to the state of a new component.